Legal adjusting of manager of foreign procedure of bankruptcy in Ukraine - Козирєва, В. П.; Гаврилішин, А. П. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article is examined the legal adjusting of participation of manager by foreign procedure of bankruptcyin matters of bankruptcy and realization of collaboration with foreign courts on the basis of Law andinternational agreements, consent to obligation of which was given by the Verkhovna Rada of Ukraine.